2018
DOI: 10.1259/bjr.20180101
|View full text |Cite
|
Sign up to set email alerts
|

Detection of noncalcified breast cancer in patients with extremely dense breasts using digital breast tomosynthesis compared with full-field digital mammography

Abstract: Breast density-tailored screening for breast cancer in females is of great interest. 1 Breast density is a predictor of breast cancer; it reduces the sensitivity of mammography, leading to an increased risk of interval cancer in the screening population. 2,3 Several breast imaging modalities have been used as adjuncts to screening mammography in females with dense breasts, including ultrasound (US; handheld or automated), MRI, and the more recently applied digital breast tomosynthesis (DBT). DBT is an emerging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(25 reference statements)
0
9
0
3
Order By: Relevance
“…Results showed no improvement in observer performance with the addition of DBT. Later studies concluded that observer performance increases with the addition of DBT to DM when using more advanced Hologic models 13,16,3543. Specifically in the detection and characterization of invasive lobular cancers, DM&DBT significantly increases sensitivity compared to DM alone 44…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosymentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed no improvement in observer performance with the addition of DBT. Later studies concluded that observer performance increases with the addition of DBT to DM when using more advanced Hologic models 13,16,3543. Specifically in the detection and characterization of invasive lobular cancers, DM&DBT significantly increases sensitivity compared to DM alone 44…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosymentioning
confidence: 99%
“…It should be noted that the three latter studies have in common a relatively small number of participants (100–200 women). Specifically, for “extremely dense breasts” Yi et al35 found a non-statistically significant difference in the specificity of the systems.…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosymentioning
confidence: 99%
See 1 more Smart Citation
“…Digital breast tomosynthesis (DBT) provides quasi-3D imaging of the breast, so it reduces the superimposition of breast tissue and improves cancer detection. Previous studies showed that DBT improved the sensitivity, specificity, and accuracy of full-field digital mammography by reducing the recall rates and increasing the cancer detection rates [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la sensibilidad global de este método, que va del 75 al 85%, puede llegar a disminuir hasta un 30-50% en mujeres con senos densos (9). Por lo tanto, se ha evaluado la realización de técnicas complementarias como la ecografía, la resonancia magnética y la tomosíntesis (10).…”
Section: Introductionunclassified